Gradual carbon doping of graphitic carbon nitride towards metal-free visible light photocatalytic hydrogen evolution. Issue 31 (25th July 2018) - Chen, Zhou; Fan, Ting-Ting; Yu, Xiang; Wu, Qiu-Ling; Zhu, Qiu-Hui; Zhang, Li-Zhong; Li, Jian-Hui; Fang, Wei-Ping; Yi, Xiao-Dong
Abstract : A novel hydrothermal-conjugate-copolymerization strategy has been developed for the preparation of a carbon-rich g-C3 N4 photocatalyst. Abstract : Efficient and economical photocatalysts for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are required to replace expensive metal-based catalysts used in water splitting devices. Herein, we have developed an inexpensive route to synthesize a carbon-rich graphitic carbon nitride (C-rich g-C3 N4 ) with both nitrogen vacancies and a porous structure, which, as a highly efficient photo-induced water splitting catalyst, can meet current demands. The effects of the porous structure, nitrogen vacancies and rich amount of carbon on the electronic band structure and charge transport of g-C3 N4 are systematically elucidated. The C-rich g-C3 N4 can not only effectively enhance the absorption of visible light, but can also improve the majority carrier mobility and promote photoelectron transport through the defect-induced mid-gap and multiple conductive carbon rings, thus synergistically elongating the diffusion length and lifetime of the photocarriers. Importantly, the metal-free C-rich g-C3 N4 photocatalyst not only demonstrates a higher solar-driven hydrogen production performance, which is over 20.5 times that of pristine g-C3 N4, but also exhibits an outstanding stability with minimal loss of catalytic activity.